Cinemas de rua: sociabilidades, decadência e moralidade em Maceió (1960-1980) - Vilela, Beatriz Souza (2017)
Taking the sociabilities of street cinemas as the focus of a socio-historical procedural approach, the aim of this work is to understand the dynamics of transformation of the eroticsexual senses attributed to the exhibition rooms. In the light of the figurative-procedural perspective, we are interested in the expressive increase of the sessions with exhibitions of films considered erotic and pornographic in the cinemas Lux, Ideal and Plaza, between the years 1960 to 1980, in Maceió. Throughout the investigation, we noticed that the frequent exhibition of these films brought new limits shaping the visual experience in the exhibition rooms. The images of the films combined with the ambience provided by the rooms contributed to the spectators to weave new sociabilities, such as casual encounters with a lot of intimacy, such as the achievement of a partner for the practice of sexual activities, or even self-satisfaction as practice masturbatory. These new forms of leisure, which we call erotic-permissive erotic sociabilities, reconfigured the sessions, also imparting the possibility of being a space of sexual satisfaction. The question is not purely economic. From the viewer's point of view, we can observe that he went to the halls in search of a specific type of sexual satisfaction, supported mainly by visual gratification, since the rooms were already part of the erotic-sexual life of the city. We noticed that there was a change in the economy of desires, although the films were shown in all cinemas in the city, certain public profiles, such as those formed by gays and prostitutes, were marginalized, being restricted to neighborhoods that concentrated - and still concentrate - other types of peripheral symbolic economies, such as prostitution, illicit drug market, stolen objects, that is, in a stronghold of the marginalized. In this way, when evaluating how productions reverberated in the exhibition spaces, that is, how the films mediated sociabilities that shaped the rooms with new senses, we emphasize that the exhibition of pornographic and erotic films and the erotic-sexual sociabilities contributed to sociabilities in the theaters of street cinemas and provided new types of social spaces.